Comparative Evaluation of Lipofectamine and Dendrimer for Transfection of Short RNA Into Human T47D and MCF-10A Cell Lines - Zohreh Jahanafrooz; Behnaz Bakhshandeh; Erfan Shirzadi (Tabriz University of Medical Sciences, 2023)
Purpose: Non-viral transfection approaches are extensively used in cancer therapy. The future of cancer therapy lies on targeted and efficient drug/gene delivery. The aim of this study was to determine the transfection yields of two commercially available transfection reagents (i.e. Lipofectamine 2000, as a cationic lipid and PAMAM G5, as a cationic dendrimer) in two breast cell lines: cancerous cells (T47D) and non-cancerous ones (MCF-10A). Methods: We investigated the efficiencies of Lipofectamine 2000 and PAMAM G5 for transfection/delivery of a labeled short RNA into T47D and MCF-10A. In addition to microscopic assessments, the cellular uptakes of the complexes (fluorescein tagged-scrambled RNA with Lipofectamine or PAMAM dendrimer) were quantified by flow cytometry. Furthermore, the safety of the mentioned reagents was assessed by measuring cell necrosis through the cellular PI uptake. Results: Our results showed significantly better efficiencies of Lipofectamine compared to PAMAM dendrimer for short RNA transfection in both cell types. On the other hand, MCF-10A resisted more than T47D to the toxicity of higher concentrations of the transfection reagents. Conclusion: Altogether, our research demonstrated a route for comprehensive epigenetic modification of cancer cells and depicted an approach to efficient drug delivery, which eventually improves both short RNA-based biopharmaceutical industry and non-viral strategies in epigenetic therapy.